Husk Tomato (Physalis ixocarpa Brot.) Waste as a Promising Source of Pectin: Extraction and Physicochemical Characterization. Issue 7 (6th June 2017) - Morales‐Contreras, Blanca Elizabeth; Contreras‐Esquivel, Juan Carlos; Wicker, Louise; Ochoa‐Martínez, Luz Araceli; Morales‐Castro, Juliana
Abstract: Husk tomato ( Physalis ixocarpa Brot. var. Rendidora) waste was evaluated as a source of specialized pectin, and pectin extracted from this waste was characterized physicochemically. Fruit was blanched for 10 or 15 min and extracted in 0.1 N HCl for 15 to 25 min. Extracted pectin was subjected to physicochemical analysis. For all extraction conditions, the percentage of anhydrogalacturonic acid exceeded 60%, indicating that husk tomato was a good source of pectin. The degree of esterification of pectin molecules was 63% to 91%. The amount of extracted pectin decreased with increasing extraction time. The apparent viscosity of husk tomato pectin showed the characteristic behavior of pseudoplastic fluids. Neutral sugars were identified, and the amounts of 6 sugars (fucose, rhamnose, arabinose, galactose, glucose, and xylose) were quantified. Sugars identified in husk tomato pectin and present in the Rhamnogalacturonan I region, arabinose, galactose, and rhamnose suggest a highly branched structure, which will influence its future applications. Molecular weight values were 542 to 699 kDa, exceeding molecular weight values reported for commercial citrus pectins from 134 to 480 kDa. The extraction process significantly ( P < 0.05) influenced the physicochemical properties of pectin. Up to 19.8% from the total amount of pectin in the husk tomato was extracted by 10 min of blanching and 20 min of a more heat treatment. Our findings indicate that husk tomato can be a good alternative source of pectin having highly distinctive physicochemical characteristics.